2020
DOI: 10.1515/ntrev-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Superior Fe x N electrocatalyst derived from 1,1′-diacetylferrocene for oxygen reduction reaction in alkaline and acidic media

Abstract: Although Fe–N/C catalysts have received increasing attention in recent years for oxygen reduction reaction (ORR), it is still challenging to precisely control the active sites during the preparation. Herein, we report FexN@RGO catalysts with the size of 2–6 nm derived from the pyrolysis of graphene oxide and 1,1′-diacetylferrocene as C and Fe precursors under the NH3/Ar atmosphere as N source. The 1,1′-diacetylferrocene transforms to Fe3O4 at 600°C and transforms to Fe3N and Fe2N at 700°C and 800°C, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Studies have shown that graphite N increased the limiting current density. [4,5,32,33] Combined with our electrochemical measurements result, The limit current density of the FePc/PSAC-3/1 is 5.5 mA cm À 2 , which is significantly higher than FePc (3.1 mA cm À 2 ). The increasing trend of graphite N's content is consistent with the increase of limiting current density, so such high level of graphitic nitrogen in FePc/PSAC-3/1 is considered to be responsible for the ideal ORR activity.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Studies have shown that graphite N increased the limiting current density. [4,5,32,33] Combined with our electrochemical measurements result, The limit current density of the FePc/PSAC-3/1 is 5.5 mA cm À 2 , which is significantly higher than FePc (3.1 mA cm À 2 ). The increasing trend of graphite N's content is consistent with the increase of limiting current density, so such high level of graphitic nitrogen in FePc/PSAC-3/1 is considered to be responsible for the ideal ORR activity.…”
Section: Resultssupporting
confidence: 69%
“…[1,2,29,30] We decomposed the high-resolution XPS N 1s spectra into four component peals at 398.6, 399.7, 401.2, 403.0 eV. The four peaks can be assigned to pyridinic N, pyrrolic N, graphitic N, and oxide N, respectively [3][4][5][6][31][32][33][34] (Figure 2c). The amount of pyridinic N in PSAC is 8.1 %, and there is almost no pyrrolic N in PSAC (Figure S4, Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therein, the peaks at 711.1 and 717.1 eV can be ascribed to the Fe 2+ and Fe 3+ 2p 3/2 orbitals, respectively, of Fe–N species, while the peaks at 724.1 and 727.0 eV represent the Fe 2+ and Fe 3+ 2p 1/2 orbitals, respectively, of Fe species in the Fe–N configuration . The peak at 708.2 eV demonstrates the existence of zero-valence metallic Fe . The high-resolution N 1s XPS spectrum (Figure c) of Fe 4 N–Fe@N-C/N-KB demonstrates the coexistence of N atoms in five configurations, viz., pyridinic-N (398.5 eV), Fe–N (398.9 eV), pyrrolic-N (399.5 eV), graphitic-N (401.0 eV), and oxidized-N (402.6 eV) .…”
mentioning
confidence: 97%
“…The Fe signal of Fe 4 N–Fe@N-C/N-KB (Figure b) can be fitted with five peaks. Therein, the peaks at 711.1 and 717.1 eV can be ascribed to the Fe 2+ and Fe 3+ 2p 3/2 orbitals, respectively, of Fe–N species, while the peaks at 724.1 and 727.0 eV represent the Fe 2+ and Fe 3+ 2p 1/2 orbitals, respectively, of Fe species in the Fe–N configuration . The peak at 708.2 eV demonstrates the existence of zero-valence metallic Fe .…”
mentioning
confidence: 97%